The history of science in the nineteenth century - Spangenburg, Ray. 1939-; Moser, Diane, 1944- (New York, NY : Facts on File, 1994)
Examines the role of science in the Industrial Revolution, its establishment as a popular discipline, and discoveries in the areas of atoms and the elements, chemistry, evolution, and energy.
Includes bibliographical references (p. 123-129) and index.
Keywords: Science -- History -- 19th century -- Juvenile literature; Science -- History